Pharmacologic Prevention of Human Immunodeficiency Virus in Women. Issue 4 (April 2015) - Hong, Jennifer N.; Farel, Claire E.; Rahangdale, Lisa
<x xml:space="preserve">Abstract</x> Importance Obstetricians and gynecologists (Ob-Gyns) play a crucial role in efforts to detect and prevent human immunodeficiency virus (HIV) infection in women. Multiple strategies can be implemented into general practice as part of a comprehensive primary women's health care agenda. Educational and behavioral strategies to reduce HIV acquisition in women can now be supplemented with pharmacologic measures. Objectives This article aimed to review the literature regarding preexposure prophylaxis (PrEP) for HIV prevention in women. After reading this article, readers should be able to describe available methods to prevent HIV acquisition in women, select appropriate candidates for PrEP, and outline the steps necessary for initiation of PrEP. Evidence Acquisition A review of the available literature was obtained by a PubMed search of HIV prevention, women, preexposure prophylaxis, and PrEP. Additional information was obtained from the Centers for Disease Control and Prevention; the American Congress of Obstetricians and Gynecologists; and expert opinion in the fields of obstetrics and gynecology, infectious diseases, and reproductive infectious diseases. Results This review of the literature summarizes the efficacy of PrEP in HIV prevention and identifies limitations and barriers of PrEP. Women who are at risk for HIV acquisition and candidates for PrEP are clearly defined. Certain populations face unique challenges in HIV prevention and the administration of PrEP, and clinical guidelines and references are provided. This article provides a practical guide for the initiation, maintenance, and discontinuation of PrEP for the general Ob-Gyn. Conclusions Preexposure prophylaxis is an effective measure to prevent HIV in women. The Ob-Gyn plays a key role in the identification of at-risk women and the initiation of HIV prevention. Relevance This information is relevant to general Ob-Gyns and other women's health providers. Target Audience Obstetricians and gynecologists, family physicians Learning Objectives After participating in this activity, physicians should be better able to describe available methods to prevent HIV acquisition in women; select appropriate candidates for HIV PrEP; and outline the steps necessary for initiation of PrEP.